2015
DOI: 10.1242/dev.116533
|View full text |Cite
|
Sign up to set email alerts
|

Force production and mechanical accommodation during convergent extension

Abstract: Forces generated within the embryo during convergent extension (CE) must overcome mechanical resistance to push the head away from the rear. As mechanical resistance increases more than eightfold during CE and can vary twofold from individual to individual, we have proposed that developmental programs must include mechanical accommodation in order to maintain robust morphogenesis. To test this idea and investigate the processes that generate forces within early embryos, we developed a novel gel-based sensor to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 42 publications
(40 reference statements)
4
68
0
Order By: Relevance
“…Alternatively, gel sensors can be external instead of internal to yield accurate tissue-scale force determinations. For example, embedding Xenopus embryo tissue in soft agarose gels of differing stiffness has shown that dorsal tissues undergoing convergent extension upregulate force production when embedded in a stiffer microenvironment (Zhou et al, 2015).…”
Section: Isolatedmentioning
confidence: 99%
“…Alternatively, gel sensors can be external instead of internal to yield accurate tissue-scale force determinations. For example, embedding Xenopus embryo tissue in soft agarose gels of differing stiffness has shown that dorsal tissues undergoing convergent extension upregulate force production when embedded in a stiffer microenvironment (Zhou et al, 2015).…”
Section: Isolatedmentioning
confidence: 99%
“…These protrusions attach to and apply tractional forces to neighboring cells as the cell shortens, pulling cells between one another in support of intercalation. As the cells wedge between one another they generate an extension force of between 0.6 and 5 μN as measured in smaller dorsal tissue isolates or larger whole axial/paraxial explants, respectively (Moore, 1994;Moore et al, 1995;Zhou et al, 2015). The forces generated during Xenopus CE are tissue autonomous and internally generated (Keller and Danilchik, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Whether examined in vitro or in vivo, these cues come in many forms; generally they can be categorized as passive stimuli that occur within the microenvironment surrounding each lineage 79 or as active forces that are directly applied to cells by other cells or fluids. 1013 For the former case, cells must directly probe the environment through myosin-mediated contractions to sense changes in their surroundings and use the mechanical feedback it provides to elicit changes in cell behavior. 14,15 Conversely the latter case requires the cell to remodel internally or migrate to transmit the load, 16 a process that could activate similar molecular mechanisms.…”
mentioning
confidence: 99%
“…14,15 Conversely the latter case requires the cell to remodel internally or migrate to transmit the load, 16 a process that could activate similar molecular mechanisms. 15 Regardless of their type and mechanism, these cues can be studied in model organisms 10 or built into protocols to direct stem cell specification or to test their influence more generally as a cue on cell behavior. 17 Although significant evidence from developmental biology exists on soluble gradients, there is growing evidence using unique physical assays ex vivo and engineered microenvironments in vitro that mechanical cues and their interplay with chemical signals influence specification, which we will focus on here.…”
mentioning
confidence: 99%